PERANCANGAN DAN PENGEMBANGAN PERANGKAT LUNAK PENGENDALIAN PRODUKSI GRAFIKA - Antono Adhi; Adi Susanto (Jurnal Ilmiah Dinamika Teknik, 2012)
Graphic is one of the most important industries in the world and also in Indonesia. Most of entire human life cannot be separated from graphic product. Newspaper, books, invitation, etc. are the part of it. But for the graphic industrial, graphic process still must be managed well for efficiency and effectively in order to decrease cost. For handling that problem we must develop good procedure, control the production and develop an information system based on computer to manage it. By doing this, the process of graphic industry will produce good gain.   Keywords: graphic, production control, information system